Eating attitudes and body image concerns among female athletes from aesthetic sports - Aleksić Veljković, Aleksandra; Đurović, Dušanka; Biro, Filip; Stojanović, Katarina; Ilić, Predrag (Annales Kinesiologiae, 2020)
Purpose: Research has suggested that in female athletes from aesthetic sports the prevalence of disordered eating attitudes is higher than in female athletes from other sports, mainly due to sport related factors like extreme training and practicing sports associated with high pressure and the idea that “being thin leads to success”. The study was conducted to examine the prevalence of disturbed eating attitudes and their relationship with body image concerns in aesthetic and non-aesthetic female athletes. Methods: 54 female athletes from aesthetic sports (synchronized swimming, artistic and rhythmic gymnastics, and dance), as well as 66 female athletes from non-aesthetic sports (volleyball, track and field, and soccer), completed the Eating Attitudes Test, the Body Shape Questionnaire, and the Figure Rating Scale (a visual scale used to assess body image dissatisfaction and body image dissatisfaction in relation to sport). Results: The results indicated that aesthetic athletes scored significantly higher than those involved in non-aesthetic sports in Dieting, and in Body Image Dissatisfaction. Moreover, aesthetic athletes demonstrated significantly lower BMI mean scores. Significant correlations were found between Body Mass Index and Oral Control, Body Image Dissatisfaction and Body Image Dissatisfaction in relation to Sport, and between Eating Attitudes Test and the Body Shape Questionnaire results in aesthetic athletes. Furthermore, significant associations were found between Body Mass Index and Body Shape Questionnaire, Body Image Dissatisfaction and Body Image Dissatisfaction in relation to Sport, and Eating Attitudes Test and Body Shape Questionnaire in non-aesthetic athletes. Conclusion: The study confirmed the relationship between body image concerns and pathological eating attitudes among female aesthetic sport athletes.